Physico-chemical characteristics and dissolved trace metals in the Pahang River Estuary, Malaysia - Yunus, Kamaruzzaman; Abdurahman, Siti Waznah; Mohd Yusuf, Nurulnadia (Oriental Scientific Publishing Co., 2011)
Water samples from Pahang River estuary were analysed for Cu, Pb, Zn and Cd at 63 stations during the monson and non-monsoon seasons. Concentrations ranges of dissolved metals in the Chukai estuary were relatively low compared with other estuaries and are not significantly influenced by seasonal changes. Concentration of Cu in both monsoons ranged from 0.57 – 1.01 μgl-1, Pb ranged 0.88 – 1.34 μgl-1, Zn ranged from 9.96 – 12.8 μgl-1 and Cd ranged from 0.09 – 0.18 μgl-1. On the whole, trace metal concentrations in the dissolved metals behave conservatively and are mostly controlled by the natural processes. The estuary remained marine dominated during non-monson seasons, whereas freshwater dominance prevailed during monsoon seasons. The temperatures of surface and bottom waters are almost uniform or even identical at times while pH has an inverse relationship with salinity.